Do temperate tree species diversity and identity influence soil microbial community function and composition?. Issue 19 (30th August 2017) - Khlifa, Rim; Paquette, Alain; Messier, Christian; Reich, Peter B.; Munson, Alison D.
Abstract: Studies of biodiversity–ecosystem function in treed ecosystems have generally focused on aboveground functions. This study investigates intertrophic links between tree diversity and soil microbial community function and composition. We examined how microbial communities in surface mineral soil responded to experimental gradients of tree species richness (SR), functional diversity (FD), community‐weighted mean trait value (CWM), and tree identity. The site was a 4‐year‐old common garden experiment near Montreal, Canada, consisting of deciduous and evergreen tree species mixtures. Microbial community composition, community‐level physiological profiles, and respiration were evaluated using phospholipid fatty acid (PLFA) analysis and the MicroResp ™ system, respectively. The relationship between tree species richness and glucose‐induced respiration (GIR), basal respiration (BR), metabolic quotient (qCO2 ) followed a positive but saturating shape. Microbial communities associated with species mixtures were more active (basal respiration [BR]), with higher biomass (glucose‐induced respiration [GIR]), and used a greater number of carbon sources than monocultures. Communities associated with deciduous tree species used a greater number of carbon sources than those associated with evergreen species, suggesting a greater soil carbon storage capacity. There were no differences in microbial composition (PLFA) between monocultures and SR mixtures. The FD and the CWM of several functional traits affected both BR and GIR. In general, the CWM of traits had stronger effects than did FD, suggesting that certain traits of dominant species have more effect on ecosystem processes than does FD. Both the functions of GIR and BR were positively related to aboveground tree community productivity. Both tree diversity (SR) and identity (species and functional identity—leaf habit) affected soil microbial community respiration, biomass, and composition. For the first time, we identified functional traits related to life‐history strategy, as well as root traits that influence another trophic level, soil microbial community function, via effects on BR and GIR. Abstract : We demonstrate that both tree diversity and identity (species and functional identity—leaf habit) affected soil microbial community respiration, biomass, and composition. For the first time, we identified functional traits related to life‐history strategy, as well as root traits that influence another trophic level, soil microbial community function, via effects on BR and GIR.